The Prehistory Of Bukit Tengkorak. Sabah. Malaysia. - Stephen, Chia
In 1994-95, archaeological research was undertaken by a joint Centre for Archaeological Research Malaysia and Muzium Sabah team at Bukit Tengkorak, a prehistoric site in Sempoma, Sablih (Figure 1). Two seasons of archaeological excavations, over a period of 5 weeks, were carried out at two volcanic outcrops near the summit of Bukit Tengkorak, approximately 600 feet above sea level.